2019
DOI: 10.1186/s13104-019-4081-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the health transformation plan on cesarean section in Iran: a systematic review of the literature

Abstract: ObjectiveCesarean section (CS) is one of the most common surgical procedures in the world. In developed and developing countries, CS has grown significantly over the past decades. The Iranian Ministry of Health and Medical Education has developed a health transformation plan (HTP) in order to reduce CS rate and promote vaginal delivery. This study was conducted with the aim of reviewing the results of published studies on the impact of the HTP on CS in Iran.ResultsWe searched Embase, PubMed/MEDLINE, ISI/Web of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…The authors found a significant reduction in the rate of cesarean section in both health‐care settings . In a review study by Behzadifar et al, an overall decrease in cesarean section after the implementation of the HTP was found …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The authors found a significant reduction in the rate of cesarean section in both health‐care settings . In a review study by Behzadifar et al, an overall decrease in cesarean section after the implementation of the HTP was found …”
Section: Discussionmentioning
confidence: 94%
“…The HTP policy was aimed to expand medical coverage and provide more high‐quality services in Iran. Reducing unessential cesarean sections, which could endanger the mother's health, and increasing the propensity to choose vaginal delivery were among the important goals of the HTP …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to literature [16,[27][28][29], despite the health interventions and even some great economic and demographic changes, the rate of CS was still in an increasing trend [24]. In Iran, similarly, after implementing the special package provided by the Ministry Of Health (MOH) in 2013 to reduce unnecessary CS rate, some reduction was happened, but there is still a long way to achieve a desired rate, as noted in previous studies [30,31]. Some measures have previously been recommended to reduce the CS rate including better coordinating maternity care, collecting and measuring more data, tying Medicaid payment to quality improvement, enhancing patient-centered decision making through public reporting [28] and health instructions [32,33].…”
Section: Discussionmentioning
confidence: 95%
“…HTP implementation guidelines state that "all hospitals affiliated with the MoHME are subject to HTP" and, as such, the effects of the HTP can be observed for the above-mentioned hospitals, while private hospitals are not included in the HTP. At the time of the HTP implementation, 570 hospitals affiliated to the MoHME and 337 private hospitals were active [5,7,8]. According to the MoHME policies, public hospitals in each province should cover the needs of women and children, surgeries, public referrals, and should ensure healthcare provisions for each type of hospital (general or specialized hospital, characterized by specialized equipment) and division [5][6][7].…”
Section: Introductionmentioning
confidence: 99%